London business school small business bibliography; 1985-86 (London Business School Library LondonGB, 1987)
Contains approximately 8,500 references to literature on small business. Includes a review of literature on 'Entrepreneurship and the Entrepreneurial Personality. The subject bibliography is divided into 15 chapters covering broad subject areas including inter alia , starting new businesses, managing the on-going business, business policy and organizational development and financing the small business. An alphabetical list of authors gives the full reference to each work mentioned in the Bibliography. Appendices list journals searched and institutions from which working papers or theses have been included.
IDS